Komunikasi Antarpribadi Orang dengan HIV/AIDS (ODHA) yang Sudah Melakukan Self - Disclosure - Sukarno, Leo; Oktaviani, Roswita (Koneksi, 2020)
HIV / AIDS has become a phenomenon in the social environment of society for the last few years. Fear of stigma and discrimination from local people makes PLWHAs reluctant to reveal themselves. People with HIV who have revealed themselves must face the risk of discrimination and stigma that must be experienced in everyday life. This study aims to explain interpersonal communication among PLWHA who have done self-disclosure. The method that’s being used is a qualitative approach with case study method. The case study was conducted at ODHA Berhak Sehat Community. The data collection is done by conducting in-depth interviews with informants. Subjects in this study were people living with HIV/AIDS (PLWHA) who had opened their status for some time. In addition interviews were also conducted with specialists in sexually transmitted diseases as a research triangulator. It was found that PLWHA who have revealed status with the closest people cause a sense of trust. PLWHA do not receive discrimination, but rather supportiveness. And, an open - minded attitude from the closest person. Furthermore, the results of the study are discussed in this article. HIV/AIDS telah menjadi fenomena di lingkungan sosial masyarakat selama beberapa tahun terakhir. Orang dengan HIV/AIDS (ODHA) cenderung mendapat stigma dan diskriminasi dari masyarakat setempat. Hal ini membuat ODHA enggan mengungkapkan diri. Penelitian ini bertujuan untuk mengetahui bagaimana komunikasi antarpribadi ODHA yang sudah melakukan pengungkapan diri (self-disclosure). Penelitian ini menggunakan pendekatan kualitatif, dengan metode studi kasus. Studi kasus dilakukan pada Komunitas ODHA Berhak Sehat. Pengumpulan data dilakukan menggunakan wawancara mendalam dengan tiga ODHA yang sudah mengungkapkan status kesehatannya. Selain itu wawancara juga dilakukan kepada dokter spesialis penyakit menular seksual sebagai triangulator penelitian. Penelitian ini menemukan bahwa komunikasi antarpribadi ODHA yang sudah mengungkapkan status dengan orang terdekat menimbulkan rasa kepercayaan. ODHA tidak mendapat diskriminasi, melainkan sikap suportif. ODHA juga mendapati sikap terbuka dari orang terdekat.